DECISION SUPPORT SYSTEM FOR DETERMINING CUSTOMER FEASIBILITY TO GRANT CREDIT ON SAVING AND LOAN COOPERATIVES USING COMPARISONS OF TOPSIS AND SAW METHOD - Dian Ayu Wigasari; Jati Sasongko Wibowo (Jurnal Teknik Informatika (Jutif), 2022)
Cooperative is one of the institutions engaged in the financial sector with the business of providing savings and loan funds to its members to improve the welfare of the community's economy however currently there are still many errors that occur in the calculation process and it takes a very long time, so we need a system that can simplify the selection process in determining a decision. This research aims to support a decision support system for determining the eligibility of customers by comparing the two, so that it can be determined which method is more relevant to be implemented in the case of customers selection in grant credit. In its application, this research uses a comparison of two methods, namely the Technique for Order Preference by Similarity to Ideal Solution (TOPSIS) and Simple Additive Weighting (SAW) methods. At the system design stage, the design model and system development flow are used as an illustration in the operation of the decision support system that has been carried out based on system analysis. Based on the results of the research and discussion, it can be concluded that the comparison of TOPSIS and SAW methods has inequality in the final results that can be seen from the ranking process. The test results show that the SAW method produces a value of 0.82% for customers named lintang with the highest, while TOPSIS with a value of 0.65% for highest value, so that the SAW method is more recommended in providing solutions to the decision support system.